2019
DOI: 10.1038/s41375-019-0625-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient treatment of murine acute GvHD by in vitro expanded donor regulatory T cells

Abstract: Acute graft-versus-host disease (aGvHD) is a frequent complication after allogeneic bone marrow/stem cell transplantation (BMT/SCT) induced by co-transplanted alloreactive conventional donor T cells. We previously demonstrated that the adoptive transfer of donor CD4+CD25+Foxp3+ regulatory T cells (Treg) at the time of BMT prevents aGvHD in murine models. Yet, the therapeutic potential of donor Treg for the treatment of established aGvHD has not yet been studied in detail. We now used in vitro expanded phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 61 publications
1
33
0
1
Order By: Relevance
“…Currently, the application of donor regulatory T cells ameliorates the clinical and histologic symptoms of aGVHD and significantly enhances survival. It prevents aGVHD and it is effective for the treatment of life-threatening complications [31]. The cumulative incidences of EBV and CMV infections were significantly higher in the AD than in the MSD group (all P < 0.001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, the application of donor regulatory T cells ameliorates the clinical and histologic symptoms of aGVHD and significantly enhances survival. It prevents aGVHD and it is effective for the treatment of life-threatening complications [31]. The cumulative incidences of EBV and CMV infections were significantly higher in the AD than in the MSD group (all P < 0.001).…”
Section: Discussionmentioning
confidence: 97%
“…Transplantation related complications are the main determinants of survival; particularly, GVHD may be one of the most important factors affecting survival and prognosis [29][30][31]. We compared the occurrence of complications between the AD and MSD groups.…”
Section: Discussionmentioning
confidence: 99%
“…Treg populations including natural Tregs (nTregs) and iTregs ameliorate GvHD severity by suppressing cytotoxic T cells (15,19,50), and Treg deficiency after allo-HCT has been associated with severe aGvHD (51). Previous studies have shown that β2-AR signaling induces Treg immunosuppressive functions through an increase in CTLA-4 expression and a decrease in IL-2 levels (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, increased "priming" of all T-cell subsets reversed in patients with severe GVHD with typical lymphopenia, who received more intensive immunosuppressive therapy (Murase et al, 2014). Based on the characteristics of Tregs, adoptive Tregs transfer has prevented and treated GVHD (Mancusi et al, 2019;Riegel et al, 2020).…”
Section: Regulatory T Cellsmentioning
confidence: 99%